Tolerability of zotepine in Indian patients: Preliminary experience - Bishnoi, Ram Jeevan (Medknow Publications & Media Pvt Ltd, 2010)
Zotepine is an antipsychotic used in Japan and Europe for years and recently being introduced in Indian markets. It is claimed to be particularly effective for negative symptoms, and somnolence and weight gain are the most common side effects. Our aim is to share our clinical experience of use of zotepine with respect to its tolerability. We reviewed the first 10 patients who were prescribed zotepine at our center.